A condição juvenil dos jovens trabalhadores da Cruz Vermelha Brasileira no campus Pampulha da UFMG - Symaira Poliana Nonato (2013)
This paper is the result of a research realized with young people from Cruz Vermelha Brasileira (CVB) that work at Universidade Federal de Minas Gerais (Campus Pampulha). The present research focus was related with analyses regarding young workers, trying to comprehend specifically possible repercussions came from works on their school experiences and also the construction of projects involving young workers future. Theoretical bases used to develop this research came from reflections upon sociology of youth and sociology of education. The investigation was based on a quantitative approach, mixing it with personal techniques with quantitative research, considering the aim: to comprehend how is the condition of young people from CVB, specially facing their reality as workers. In order to achieve this goal we have used different instruments for data collecting. First, we have worked on localization of young people and their place of work inside campus. The observation lasted one year, once a week, during the course of a project developed with 40 young people, but we also realized, at the same time, observations regarding the everyday routine in all of the places they worked in. The questionnaire has been administrated by the researcher reaching 149 young people, what has optimized the study, since it has provided extra information. With all this we could perceive that the young people condition is marched by ambiguity that the study presents. The profile of young worker includes: routine, uncertainty regarding future projects and the condition of young people and also as student, is limited by worker condition. The school has built itself the image of a place for helping conquering better jobs warranty of a better future. Then, this concept of schooling is connected with the idea of improving life, prosperity. As per future projects, we can highlight that they do dialog sometimes with furthering studies, sometimes with the search for better insertions in labor marketing, both seen as possibilities of acting in favor of the family financial support. Finally we can say that the study in Brazil, as the school announces, make youths, bringing brands ambiguous to the experience of the juvenile condition